Noncompact myocardium with dilated phenotype: differences in comparison with other forms of dilated cardiomyopathy. (14th October 2021) - Blagova, O; Pavlenko, E V; Varionchik, N V; Sedov, V P; Polyak, M E; Zaklyazminskaya, E V
Abstract: Introduction: Noncompact myocardium (NCM) is a cardiomyopathy with various genetic causes and clinical manifestations; its relationship with other forms of dilated cardiomyopathy (DCM) and its impact on prognosis are unclear. Objective: To study the place of NCM in the structure of DCM, its clinical features and influence on prognosis in comparison with other forms of DCM syndrome. Methods: The NCM registry includes 125 patients, mean age 46.4±15.1 years, 74 men and 51 women, mean follow-up 14 [4.0; 41.0] months. The DCM registry included 365 patients, mean age 46.4±15.1 years, 253 men and 112 women, mean follow-up 14 [5; 43.75] months. The examination included ECG, ECG Holter monitoring, echocardiography, blood anti-heart antibody level evaluation, and additionally cardiac CT, MRI, DNA diagnostics (in the MYH7, MYBPC3, TPM1, TNNI3, TNNT2, ACTC1, TAZ, ZASP (LDB3), MYL2, MYL3, DES, LMNA, EMD, TTR gene panel), coronary angiography, right ventricular endomyocardial biopsy. Results: The proportion of patients with DCM phenotype in the NCM registry was 40% (n=49), another 11% (n=15) had DCM syndrome diagnosed simultaneously with acute/subacute myocarditis. Lethality in these subgroups was 12.2% and 33.3%, respectively, and was significantly higher than in asymptomatic, ischemic and arrhythmic variants of DCM. In the DCM registry, the proportion of patients with NCM was 21% (n=78), and increased left ventricular (LV) trabecularity was detected in another 18% (n=64). DCM patients with and without NCM did not differ by baseline echocardiographic parameters, heart failure class, and cardiotropic therapy. Pathogenic mutations were detected in 14% of DCM patients with NCM and only 3% of other patients with DCM (p<0.001). Only in patients without NCM the presence of mutations had a significant effect on lethality. The patients with NCM compared with the others DCM patients showed significantly lower increase in EF in early and late period (from 31.0±10.2 to 34.8±11.0 and 37.1±10.9% vs from 31.8±9.7 to 38.8±11.3 and 42.3±12.4%, p<0.05 vs 05 and <0.01, respectively), a greater incidence of PVBs (1568 [105; 7000] vs 543.5 [77.75; 3194], p<0.05), appropriate defibrillator shocks and sudden deaths (17.9 vs 5.9%, p<0.001), intracardiac thrombosis (21.8 vs 13.5%, p=0.069) despite a greater frequency of anticoagulants (73.1 vs 57.4%, p<0<05). There were no significant differences in death (19.2 vs 18.5%) and transplantation (7.7 vs 3.8%) between patients with and without NCM. There were no cases of NCM regression. Conclusion: NCM is an independent form of DCM syndrome, which is characterized by higher frequency of pathogenic mutations, arrhythmic events, worse response to cardiotropic therapy, higher frequency of intracardiac thrombosis. The absence of mortality differences can be explained by the higher frequency of preventive interventions in this category of patients with DCM (prescription of anticoagulants, defibrillator implantation, heart transplantation). FUNDunding Acknowledgement: Type of funding sources: None.